Регулируемые электроприводы толстолистового прокатного стана и качество питающей сети - Помазановский, О. А.; Промышлянский, М. А.; Скидан, Н. Н. (НТУ "ХПИ", 2010)
In this article have been examined the questions of quality of power system during engineering of plate mill with application the equipment of ABB Ltd.
Adjustable drives of plate mill and quality of power system
Keywords: электродвигатель переменного тока; преобразователь частоты; тиристор; охлаждение водяное; трансформатор; модуляция широтно-импульсная